2020
DOI: 10.1111/sji.12989
|View full text |Cite
|
Sign up to set email alerts
|

T cell immunobiology and cytokine storm of COVID‐19

Abstract: 2019 coronavirus disease (COVID-19) presents as a newly recognized pneumonia and could rapidly progress into acute respiratory distress syndrome which has brought about a global pandemic. Until now, no curative therapy has been strongly recommended for COVID-19 except for personalized supportive care. T cells and virus-specific T cells are essential to protect against virus infection, including COVID-19. Delayed immune reconstitution (IR) and cytokine storm (CS) remain serious obstacles for the cure of COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 107 publications
(145 reference statements)
6
88
1
5
Order By: Relevance
“…It remains to be shown that COVID-19 patients with anxiety have higher IL-17/ IL-17A, and if there is correlation between the levels of IL-17A and the severity of anxiety. Given what is already known about the role of IL-17 in anxiety in humans and mice, and the presence of cytokine storm in COVID-19 with increased levels of IL-17 (Luo et al 2020;Shibabaw 2020), it can be hypothesised that IL-17 plays a pathogenetic role in anxiety in COVID-19 infection. The mechanisms through which the immune system is involved in COVID-19 in anxiety are investigated, and this will have significance for development of treatments.…”
Section: Overview Of Covid-19 Pandemicmentioning
confidence: 99%
“…It remains to be shown that COVID-19 patients with anxiety have higher IL-17/ IL-17A, and if there is correlation between the levels of IL-17A and the severity of anxiety. Given what is already known about the role of IL-17 in anxiety in humans and mice, and the presence of cytokine storm in COVID-19 with increased levels of IL-17 (Luo et al 2020;Shibabaw 2020), it can be hypothesised that IL-17 plays a pathogenetic role in anxiety in COVID-19 infection. The mechanisms through which the immune system is involved in COVID-19 in anxiety are investigated, and this will have significance for development of treatments.…”
Section: Overview Of Covid-19 Pandemicmentioning
confidence: 99%
“…Once COVID-19 enters the spleen, a series of immune responses are initiated and multiple cytokines are released. Both virus and autoimmunity damages the immune cells of the spleen, peripheral and central lymph nodes, and other lymphoid tissues [2,13,14].In an autopsy study conducted in patients who died due to COVID-19, it was reported that the volume of the spleen decreased significantly [2]. Similar autopsy findings were reported in severe acute respiratory syndrome [SARS] patients, too.…”
Section: Discussionmentioning
confidence: 67%
“…Most of the patients have mainly displayed pneumoniaassociated symptoms such as fever, cough, dyspnoea, and myalgia [1]. However, the disease may also involve other organs, such as the gastrointestinal, nervous, and cardiovascular systems [1,2]. It uses angiotensin-converting enzyme 2 (ACE2) as a host cell receptor [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severely ill and deceased COVID-19 subjects show expressively lower lymphocyte (CD8+ and CD4+ T cells) levels than the survivors [39,158]; however, with the higher neutrophil counts compared to lymphocytes [103,189]. In addition, the CD4+ and CD8+ T cells from critically ill COVID-19 patients highly express inhibitory receptor such as T-cell immunoglobulin mucin-3 (Tim-3) and Programmed cell death protein 1 (PD-1) [109,212,214]. The increased level of TNF-α, IL-6, and IL-10 is inversely correlated with the decreased T cell population [85,135] and IL-2, IL-7, IL-15, and IL-21 were reported to upregulate PD-1 expression on T cells [91].…”
Section: Covid-19 Mrna Vaccine Inflammation and Effects On Ovarian Cmentioning
confidence: 99%